Development of Game for Self-Help Toilet Learning for Children with Autism - Rahadian Kurniawan; Wuriandietry Mayang Purnamasari; Restu Rakhmawati; Dimas Panji Eka Jalaputra (Bina Nusantara University, 2018)
This study aims to develop a video game for toilet training materials as a medium for self-help learning for children with autism. Toileting skill is one of the basic self-help skills that children should master. In fact, teaching new things to children with autism is challenging. It requires a proper method to deliver the materials to these children. One of the effective learning media to teach self-help is to use visual media like video games. By using video games, children are expected to play and learn self-help skills, particularly about toileting. In addition, the video game is developed by applying certain design principles that fit with the needs of children with autism. The software is tested for its functionalities. Moreover, an implementation test is done by using observation communication analysis. Based on the results, the researchers conclude that the developed video game has implemented the proper design and materials related to toileting in accordance with the needs of children with autism. The respondents show positive results for using the video game.